(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
A number of surveys over the past couple of decades have shown that divorce has negative consequences on children. This is a challenge to study the model of parental responsibility after a divorce that corresponds to the principle of respecting the best interests of the child. In the paper, the authors make a comparative analysis of the exercise of the parental rights after the divorce de lege lata. The authors analyze the consequences of divorce on children, as well as the results of sociological research on the impact of the joint exercise of parental rights after divorce on children, which is a modern tendency in the world in recent years. This research is done in order to propose the best solutions that would be implemented in Macedonian legislation de lege ferenda. The authors believe that reforms of the Macedonian family legislation regarding the exercise of the parental right after the divorce are urgently needed, given the fact that the number of divorces in Macedonia is constantly on the rise, and our legislation has an extremely outdated conception of parenting after divorce, leading to serious problems for children and parents after the divorce.